Recent Development on Cp*Ir(III)‐Catalyzed C−H Bond Functionalization. Issue 9 (23rd January 2020) - Li, Xianwei; Ouyang, Wensen; Nie, Jianhong; Ji, Shaomin; Chen, Qian; Huo, Yanping
Abstract: Selective functionalization of ubiquitous C−H bonds of molecules would provide novel retrosynthetic insights and powerful tools for the rapid construction of molecular complexity. In this context, Cp*Ir(III) complexes have exhibited versatile reactivity towards the selective conversion of C−H bonds, with key features that include the use of readily transformable raw materials, great selectivity (chemo‐, stereo‐ and regio‐), high efficiency, mild reaction conditions and they enable late‐stage modification of complex molecules. Recently, Cp*Ir(III) catalysis has achieved a broad range of reactions such as multiple dehydrogenations and stereoselective C−X bond formations. These advancements are valuable to organometallic chemists and enable the efficient synthesis of functionalized architectures. Abstract : Homogeneous catalysis : Cp*Ir(III) complexes have emerged as versatile catalysts that enable various inert C−H bond functionalizations, featuring readily transformable starting materials, great selectivity and a broad range of reactions that could be well applicable in late‐stage modifications of biologically active molecules.